ITT640 - Wireless Networks / Faculty of Computer and Mathematical Sciences - UiTM, Faculty of Computer And Mathematical Sciences (Universiti Teknologi MARA (UiTM), 2023)
This course addresses the fundamental concept, current and emerging technologies, standards, and protocols, related to Wireless Networks. Topics covered include: Wireless Transmission Fundamentals, Wireless Medium Access Control, WPAN, WLAN, WWAN, Satellite Communications and WLAN Deployment. At the end of the course, students are required to design a WLAN using simulation software.